Podjetniško premoženje kot skupno premoženje zakoncev - Dugar, Gregor (Pravni letopis, 2015)
The Marriage and Family Relations Act (hereinafter: the ZZZDR) was created during the collective ownership period, when entrepreneurship was not yet developed in Slovenia. After Slovenia's independence in 1991 and the adoption of a new constitutional arrangement, entrepreneurship saw a rapid growth. Since the very beginnings, entrepreneurship has been taken up both by single individuals and spouses. The property of some spouses increases significantly as a result of being involved in entrepreneurship. In these cases, an equity stake in a company usually represents the largest part of common property of the spouses. With regard to property relations between spouses, the ZZZDR does not define any special rules concerning spouses' equity stake in a company. Corporate law rules do not contain any such rules either. The absence of special rules in both family and corporate legislation causes a conflict between their respective rules, making it unclear which should be given priority.
Keywords: corporation; marriage; podjetje; pravna ureditev; premoženje; zakonska zveza